Cloning and expression of coat protein gene of sweet potato leaf curl virus (splcv) - Sruthy, G S (Department of Plant Biotechnology, College of Agriculture, 2018)
The study entitled “Cloning and expression of coat protein gene of sweet potato leaf curl virus was carried out at the division of crop protection, Central Tuber Crops Research Institute, Sreekariyam, Thiruvananthapuram during 2017-2018. The objective of the study was to clone and express the coat protein gene of sweet potato leaf curl virus. Sweet potato samples with Sweet potato leaf curl symptoms were collected from the germplasm repository of ICAR-CTCRI Thiruvananthapuram and field samples from regional station Bhuvaneshwar. Initial screening of Sweet potato leaf curl virus was done with the specific partial coat protein primers which give the bands with the amplicon size of 470bp. Out of 35 samples 10 samples were shows the SPLCV positive infection. Whole genome amplification of Sweet potato leaf curl virus was done by rolling circle amplification method. PBS2KS+ vector is used in the cloning purpose. Recombinant colonies were confirmed by restriction analysis with BamHI. Sequencing was done by SPLCV specific primers PW285.2, SPG1, SPG4, M13 R and T3. Sequences shows maximum similarity (90%) with Sweet potato leaf curl Greece virus isolates (KF697069.1). For the whole coat protein gene amplification new primers were designed by adding NdeI and KpnI restriction digestion sites. Standardization of primer was done and kept melting temperature at 55.9°C for further PCR amplification. Whole coat protein gene amplification was done which give the bands at 776 bp. Eluted PCR products were cloned in PTZ57R/T vector and transformed in to DH5α cells. Plasmids were isolated from recombinant colonies and confirmation was done with restriction digestion with SacI and HindIII. Sequence analysis was done for further studies which show 98% similarity with Sweet potato leaf curl virus CTCRI isolate. The recombinant PTZ57R/T vector is restricted with SacI and HindIII is eluted and cloned into expression vectors such as pMALp5X, pET28a+ and pQE expression vectors. SPLCV-CP insert concentration was high in pET28a+, hence further expression studies pET28a+ was selected. The CP gene was cloned in pET 28a+ vector and transformed into BL21 cells. The BL21 clone containing the inframe CP gene was subjected to protein expression by IPTG induction. The protein expression was optimum at 37°C for 3 h with an IPTG